Active and recent deformation, and tectono-sedimentary structure of the offshore Algerian margin - (:unkn) unknown (My University, 2006)
Important issues in seismic hazard assessment arise from slow convergent plates that are less easy to solve than in subduction zones. North Africa is a major study area in this context to study the reactivation in compression of a complex Cenozoic passive margin. This work based on the MARADJA'03 and MARADJA2/SAMRA'05 cruises data (multibeam bathymetry, seismic-reflection, side-scan sonar, backscattering, CHIRP, gravimetry) made possible for the first time a characterization of the multi-scale structure of the offshore Algerian margin. Sedimentary (among which, sediment instabilities) and tectonic (geomorphology, folds, faults) records reveal large recent and active structures as well as the geological inheritage of the margin. Two main tectonic styles are identified: strike-slip features to the west; and reverse to the centre and east: blind faults (Plio-Quaternary) verging to the north (opposite to preexisting features) expressed as asymmetrical folds, sub-perpendicular to the convergence direction and often en echelon. These faults (minimum long-term shortening rate over all the structures: 0.1-0.6 mm/yr) may all trigger M=6-7.5 events (among them, the Khayr al Din fault near Algiers). Among them, the fault associated with the Boumerdes earthquake (21/3/2003, Mw=6.8) would continue to the surface by flats and ramps creating piggy-back basins (up to 60 km seaward) or rollovers (on the slope). A large part of the deformation resulting from NNW-SSE Africa-Eurasia convergence (~5 mm/yr at the longitude of Algiers) is accommodated at the foot of the Algerian margin, which could indicate, with the compressionnal flexure of the deep basin, a future subduction inception.
Keywords: African Research